A comparative study on the effect of intravenous Ringer lactate at 125 ml/hour versus 250 ml/hour on the duration of labour in nulliparous pregnant women - Mittal, Shivika; Gupta, Amit; Sharma, Chanderdeep; Dhatwalia, Prashant; Mittal, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Several factors may influence the progression of normal labour. It has been postulated that the routine administration of intravenous fluids to keep women adequately hydrated during labour may reduce the period of contraction and relaxation of the uterine muscle, and may ultimately reduce the duration of the labour. However, the routine administration of intravenous fluids to labouring women has not been adequately studied although it is widely practiced, and there is no consensus on the type or volume of fluids that are required, or indeed, whether intravenous fluids are at all necessary. This study was conducted to study the effect of intravenous Ringer lactate at 125 ml/hour versus 250 ml/hour on the duration of labour. Methods: In the study, patients were divided in two groups of nulliparous pregnant women in spontaneous early labour (between 3-5 cm dilatation), at term with singleton pregnancy and cephalic presentation, where one group received intravenous Ringer lactate at 125 ml/hour and the other group received Ringer lactate at 250 ml/hour. The duration of labour, mode of delivery and caesarean rates were measured in both groups along with incidence of prolonged labour and need for oxytocin augmentation. Results: The incidence of prolonged labour and oxytocin augmentation were less in the group receiving intravenous RL at 250 ml/hour but was not statistically significant. Remaining outcomes were comparable in both the groups with no outcome reaching statistical significance. Conclusions: Rate of fluid administration is one of the many variables which affects the labour outcomes. The incidence of prolonged labour and oxytocin augmentation was less in the group which received intravenous RL 250 ml/hour. There was no statistically significant difference in both groups in respect of duration of labour, mode of delivery and caesarean rates.